DEVELOPMENT IN L2 WRITING AFTER A SEMESTER OF STUDY IN AN AUSTRALIAN UNIVERSITY - Neomy Storch (Indonesian JELT, 2007)
There is a common expectation, particularly amongst international students, that studying in an English-medium university would lead to an improvement in their writing skills (as well as other language skills). However, to date there has been very little research about the impact of studying in an English medium university on the development of learners’ writing. This paper reports on study which was part of a larger project. The larger project, using a test-re-test design, investigated whether the reading and writing skills of international students improved after one semester of study in an Australian university. The study reported here analysed the writing test scripts of 20 students whose global writing scores indicated improvement in writing and who had not accessed any language support during the semester. A range of quantitative and qualitative measures were used to analyse the data, including measures of linguistic fluency, accuracy and complexity. The study found that the greatest improvements occurred in how learners structured their writing and developed their ideas.  There was also a marked improvement in the formality of learners’ language, but less evidence of improvement in language accuracy and complexity. These findings suggest that some aspects of written language may need more explicit language instruction in order to improve. Keywords: English    medium    university,   writing   test  scripts,linguistic   fluency,   linguistic   accuracy,   linguistic complexity, explicit language intruction.